E-Commerce in Education Programmes a Way to Solve Unemployment Amongst Education Graduates - Gretrude Jeremiah Udoh; Usenobong D. Edem; Uduak. E. Antai (MultiTech Publisher, 2024)
This paper argues the need to include e-commerce as a subject in Education programs to enhance our students’ employment chances of education graduates in Nigeria. The study was conducted using the survey research method. The population of the study comprises 330 Business Education students in two universities in Anambra state. The research was carried out in Nnamdi Azikiwe University and students of Abia State University. A questionnaire was used for data collection and a sample of 130 Business Education students was collected for the study, out of which 90 were dully filled and completed. The findings revealed that the knowledge of e-commerce skills has great usefulness and importance on companies and enterprises giving the graduates of Business education an employment advantage. E-commerce education has a positive impact on the Business Education program. The study recommended that the program should be given their rightful place in the Business Education program and they should also be accorded equal recognition as other programs in the Business Education Department.